The Present and its Remaining Art, Literature and Image in the Contemporary Aesthetics - Neuburger, Ana (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In the last decades, the field of aesthetics and the studies on art have participated in a series of transformations and movements that brought together two issues: the announcements about the end of art (and even more broadly, the end of meaning, of history, literature) and the debates on the post-autonomy of art. Based on the critical and theoretical contributions of Nelly Richard, Jacques Rancière, Giorgio Agamben, among others, this article explores the emergence of the notion of image in the contemporary scenario in order to point out the senses that advocate the expiration of art or, its opposite, an impulse of innovation of the forms. Faced with the opening of the relationship between art and literature, this displacement is possible to read in the way that contemporary Argentine criticism composes a constellation of meanings between image, writing and the present.